1991
DOI: 10.1002/1097-0142(19910601)67:11<2935::aid-cncr2820671138>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral metastases as first symptom of bronchogenic carcinoma. A prospective study of 37 cases

Abstract: Among the patients showing evidence of cerebral metastases without previously known cancer history, lung cancer has been found 37 times as the primary tumor in our institution. There were 34 men and three women and all but two were heavy smokers. Only one presented at diagnosis with thoracic symptoms but the chest radiograph was abnormal in 34. The histologic type of the primary tumor was obtained in 32 cases as a result of thoracic investigations and in five cases from metastatic tumor tissue. The primary tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The impact of gender on survival has not been an issue until recently because reported case material until the late 1980s was dominated by men. 55,67,70 In our series, the number of men and women was similar (ratio 1:1) and women survived longer by 4.3 months. Similarly, in most published series of patients who have undergone surgical treatment of primary lung cancer, women have had a better prognosis than men.…”
Section: Gender Of Patientssupporting
confidence: 53%
See 1 more Smart Citation
“…The impact of gender on survival has not been an issue until recently because reported case material until the late 1980s was dominated by men. 55,67,70 In our series, the number of men and women was similar (ratio 1:1) and women survived longer by 4.3 months. Similarly, in most published series of patients who have undergone surgical treatment of primary lung cancer, women have had a better prognosis than men.…”
Section: Gender Of Patientssupporting
confidence: 53%
“…Others have reported similar findings. 5,32,69,70 In general, the median interval between the diagnosis of lung cancer and the discovery of brain metastases is 6 months, but 10% of our patients with adenocarcinoma did not receive a diagnosis of brain metastasis until more than 2 years after diagnosis of their primary tumor. For five patients, the interval was even longer-more than 5 years-a time period that was also reported by Komaki and colleagues.…”
Section: Histopathological Findingsmentioning
confidence: 85%
“…Patients with single brain metastasis who underwent a gross total resection and WBRT displayed survival patterns similar to those reported by most authors for patients with single brain metastasis both from unknown and known primary tumour treated by surgery and radiotherapy. These had a median survival of 9-14 months with 30-53 % alive at 1 year and up to 20-25 % alive at 2 years [5,15,18,21,22,25,26,28,29,31,33]. Le Chevalier et al [14] and Eapen et al [8] reported a poorer prognosis with a median survival of 6 months, 18-20 % alive at 1 year and 5,4 % at 2 years, but half of the patients had not received surgery [14] or only incomplete surgery [8].…”
Section: Discussionmentioning
confidence: 68%
“…30 The squamous differentiation (metaplasia) can be accentuated in the metastatic site, which may lead to the erroneous diagnosis of primary bronchogenic squamous cell carcinoma. 31 In addition, both mammary and pulmonary adenocarcinomas have a similar predilection for distant metastasis to the bone, liver, brain, and adrenal glands, 15,19,32,33 and metastasis of mammary carcinomas can clinically and radiographically present as a solitary lung mass with metastasis in any of the above-mentioned organs, a condition that can be interpreted as a lung cancer with distant metastasis.…”
Section: Discussionmentioning
confidence: 99%